Vegetation dynamics at the upper elevational limit of vascular plants in Himalaya - Dolezal, Jiri; Dvorsky, Miroslav; Kopecky, Martin; Liancourt, Pierre; Hiiesalu, Inga; Macek, Martin; Altman, Jan; Chlumska, Zuzana; Rehakova, Klara; Capkova, Katerina; Borovec, Jakub; Mudrak, Ondrej; et al. (Scientific reports, 2016)
A rapid warming in Himalayas is predicted to increase plant upper distributional limits, vegetation cover and abundance of species adapted to warmer climate. We explored these predictions in NW Himalayas, by revisiting uppermost plant populations after ten years (2003-2013), detailed monitoring of vegetation changes in permanent plots (2009-2012), and age analysis of plants growing from 5500 to 6150 m. Plant traits and microclimate variables were recorded to explain observed vegetation changes. The elevation limits of several species shifted up to 6150 m, about 150 vertical meters above the limit of continuous plant distribution. The plant age analysis corroborated the hypothesis of warming-driven uphill migration. However, the impact of warming interacts with increasing precipitation and physical disturbance. The extreme summer snowfall event in 2010 is likely responsible for substantial decrease in plant cover in both alpine and subnival vegetation and compositional shift towards species preferring wetter habitats. Simultaneous increase in summer temperature and precipitation caused rapid snow melt and, coupled with frequent night frosts, generated multiple freeze-thaw cycles detrimental to subnival plants. Our results suggest that plant species responses to ongoing climate change will not be unidirectional upward range shifts but rather multi-dimensional, species-specific and spatially variable.
Keywords: Indie; Biodiversity; rostliny; Climate Change; Population Dynamics; populační dynamika; klimatické změny; biodiverzita; India; Plants